Vico and Man’s Creation of Institutions: A Backward Journey to Human Root - Sasa, Michael Sunday (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2018)
This paper attempts to expose the creation of human institutions from the perspective of the thoughts of Giambattista Vico. He explains the three principles of history: religion, marriage and burial; these are principles both in the sense that they are the first things in society and in that they lie at the core of social existence. He develops a theory of the creation of human institutions that stands quite different from the theories of social contractarians. To accomplish its aim, the paper seeks to engage in a discourse by looking at man in his bestial nature and then goes on to consider how key human institutions like matrimony, burial and land cultivation was developed in human affairs. The paper then considers subsequent developments. This it does within the context of three key stages in Vico’s philosophy of history. The conclusion that is reached in the final third is that, in all the process of the creation of institutions by man, reason and perseverance won it all and held sway.